Reinstatement of Aloe mutans (Asphodelaceae subfam. Alooideae), a distinctive, endemic, maculate aloe from the central Limpopo province of South Africa - Smith, Gideon F.; Figueiredo, Estrela; Klopper, Ronell R. (Phytotaxa, 2024)
Until 1987, Aloe mutans (Asphodelaceae subfam. Alooideae) was accepted as a distinctive species of maculate aloe from South Africa’s Limpopo province. However, this species thereafter often has been included in the synonymy of A. greatheadii var. davyana. Recently, A. davyana was separated from A. greatheadii at the rank of species, which requires reconsideration of the taxonomic status of A. mutans. It is shown that A. mutans differs from A. davyana in several vegetative and reproductive morphological characters so warranting its recognition at the rank of species. Aloe mutans is therefore here reinstated as an accepted species. Both A. mutans and A. davyana are illustrated and an amplified description is provided for A. mutans.